Invigilation timetabling system using genetic algorithm (GA) / Shahirah Mohamed Hatim - Shahirah, Mohamed Hatim (2011)
Timetabling problem is said to be a common problem that occurred in any educational institutions. It is usually being solved manually or with the help of simple system. This problem also can be solved using a proper techniques or solutions to organize job or task in a good manner. In assigning the lecturers to invigilate the rooms, conflicts may occur. This prototype system is developed for the purpose of assigning lecturers to examination rooms during the final examination. This system is developed for the invigilators and with the objective of constructing an invigilation timetable using Genetic Algorithm. This system uses four steps of Genetic Algorithm technique which are initialization, evaluation, crossover and mutation to produce the new timetable. As a result, the system can generate a simple timetable records but with a limitation where it cannot display the name of the records. It is a hope that this system can contribute for further generation of a complete timetable.